Perfil de FSH e LH na divergência folicular em novilhas Nelore (Bos indicus) - Gimenes, Lindsay Unno (2008)
Present study aimed to evaluate gonadotropins profiles in 12 Nelore heifers, in order to test the hypothesis that FSH concentrations decrease and LH presents a transient increase during follicle selection. Blood samples from jugular vein were harvested twice daily starting at the time of ovulation (D0) until D5. Plasma samples were assayed for FSH and LH by double antibody radioimmunoassay method. LH and FSH assay sensitivity was 0,02ng/ml and 0,005ng/ml, respectively. The intraassay coefficient of variation was 13,6% and 18,8%, respectively. Data (mean±SEM) were normalized to follicle deviation and analyzed by ANOVA and by linear, cubic, and quadratic regressions. Comparisons between higher and lower FSH values were also performed by T-test. There was no effect of time in plasmatic FSH and LH circulating levels when variance analysis or regression analysis were performed. However, by T-test, FSH concentrationsreached the lowest plasmatic levels 36 (0,40±0,05ng/ml) and 60 hours (0,42±0,04ng/ml) after follicular deviation, comparatively to 36 hours before deviation, when the concentrations were maximal (0,63±0,08ng/ml). In conclusion, there is a FSH decrease, although a transient LH elevation has not been confirmed encompassing follicle deviation in Nelore females.